A STUDY ON OUTCOMES OF VARIOUS TREATMENT REGIMENS IN DRUG- RESISTANT TUBERCULOSIS - Dr. Abhijeet Yadav; Dr. Vivekanand N. Waghmare; Dr. Sharad B Sable (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background:Drug-resistant tuberculosis (DR-TB) poses a significant challenge to global public health due to its complexity in treatment and the emergence of extensively drug-resistant strains. Conventional treatment protocols have shown varying success rates, necessitating exploration into alternative regimens. Understanding the outcomes of these diverse treatment approaches is crucial for optimizing patient care and combating the spread of resistant strains.Aims & Objectives:This study aims to investigate the outcomes of different treatment regimens employed for DR-TB. Methodology:This is a record-based study in a Government Medical college in Maharashtra during the year 2020 to 2022. All adult drug resistant TB cases registered were included, giving a sample size of 258. The outcomes of all regimens were examined.Results:Out of the total 258cases, 136(52.71%) were males and 122(47.28%) were females. Majority of them 90 (34.88%) belonged to age group of 21 to 30 years. The treatment outcomes were as follows: Out of the total 258 cases, 107(41.47%) were cured , 55(21.31%) completed treatment, 3(1.16%) were treatment failed, 6(2.32%) were lost to follow up, 45(17.44%) expired before treatment completion, 41(15.89%) required change of regimen.Conclusion:Optimizing treatment strategies for DR-TB is essential for improving patient outcomes, reducing transmission, and addressing the global burden of tuberculosis.